Education and involvement of medical students in health policy as a long-term strategy to attain health goals in developing countries - Raihan, Fatimah Sarah Mohd (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: The extent of a country’s development depends on the growth of its economy, the level of literacy, as well as the advancements in public health and the national healthcare system. Barriers to a sustainable development in the health sector of a country include financial and socio-political aspects as well as intergenerational communication and transfer of knowledge. Literature on health policy training in developing nations is scarce. Methods: This scoping review was carried out through academic literature search on related articles published from 2014 to 2024, supplemented with indirectly related articles, older academic articles and recent non-academic publications where necessary due to information insufficiency - in order to answer three main research questions regarding the trend in academic interest in this topic, the landscape of health policy education for medical students in developing countries and evidence that the students’ participation in health policy roles can have a positive impact on national healthcare. Findings: 56 articles on medical students’ health policy education and involvement were retrieved, which mostly originated from developed countries. Further investigation found some records of this topic in developing countries, which enabled its discussion and comparison to its counterparts in developed nations. Conclusion: Improving the delivery of health policy education in developing countries is crucial for sowing future physicians’ interest and ability in controlling and advocating for national health issues - which is ultimately important for the development of the national healthcare structure and its capability to overcome not only short term, urgent crises, but also satisfy the long-term needs in a continuously developing nation. Novelty/Originality of this article: No literature has previously been published as an overview of health policy education and involvement of medical students in developing countries and its comparative analysis with the scenario in developed countries as a means of development goal strategy mapping.